2022
DOI: 10.3390/jcm11040951
|View full text |Cite
|
Sign up to set email alerts
|

rTMS Reduces Craving and Alcohol Use in Patients with Alcohol Use Disorder: Results of a Randomized, Sham-Controlled Clinical Trial

Abstract: (1) Background: Current evidence-based treatments for alcohol use disorder (AUD) are moderately effective. Studies testing repetitive transcranial magnetic stimulation (rTMS) in AUD commonly apply a limited number of rTMS sessions with different rTMS settings, showing inconsistent effects on craving for alcohol. This study tested the efficacy of a robust rTMS protocol on craving and alcohol use. (2) Methods: In a single-blind randomized controlled trial in recently detoxified patients with AUD, ten days of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
0
12
1
Order By: Relevance
“…Together, our findings are in line with the negative findings reported in the relatively larger studies in AUD [ 63 ] and studies conducted in nicotine use disorder [ 65 ] and cocaine use disorder [ 69 ]. However, our findings are contrary to other smaller studies that were either pilot studies [ 60 , 62 ] or did not report on follow‐up measures of alcohol use [ 59 ]. Furthermore, results of the current study are hard to compare to other studies as they did not include follow‐up periods [ 66 , 68 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Together, our findings are in line with the negative findings reported in the relatively larger studies in AUD [ 63 ] and studies conducted in nicotine use disorder [ 65 ] and cocaine use disorder [ 69 ]. However, our findings are contrary to other smaller studies that were either pilot studies [ 60 , 62 ] or did not report on follow‐up measures of alcohol use [ 59 ]. Furthermore, results of the current study are hard to compare to other studies as they did not include follow‐up periods [ 66 , 68 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Belgers and colleagues showed a group × time interaction, showing decreased craving in the active group up to 3 months' follow-up [44,59]. Differences in study samples could have had an influence on the outcomes, as Belgers et al [59] collected data from outpatients whereas the current study only included inpatients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There are very few studies which follow patients beyond the 6-month period. 38, 49 The outcomes measured include craving, impulsivity, 33 His study was based on randomized single blind sham-controlled design with one month follow-up. This was followed in 2015 by Girardi et al who performed an open label study to prove significant effect of add on TMS therapy compared to standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies have provided promising evidence that rTMS targeting the dorsolateral prefrontal cortex (DLPFC) may have the potential to alleviate craving in individuals with general substance dependence [ 38 , 39 ]. To bolster these findings, a randomized sham-control clinical trial using high-frequency rTMS to treat alcohol use disorders showed that stimulation of right DLPFC diminished both alcohol use and craving [ 40 ]. While these are promising findings, this evaluation requires further consideration as craving scales reflect a psychological construct which commonly leads to over-interpretation of results.…”
Section: Neuromodulation In Psychiatrymentioning
confidence: 99%